2020
DOI: 10.1038/s41523-020-00185-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of germline variation with the survival of women with BRCA1/2 pathogenic variants and breast cancer

Abstract: Germline genetic variation has been suggested to influence the survival of breast cancer patients independently of tumor pathology. We have studied survival associations of genetic variants in two etiologically unique groups of breast cancer patients, the carriers of germline pathogenic variants in BRCA1 or BRCA2 genes. We found that rs57025206 was significantly associated with the overall survival, predicting higher mortality of BRCA1 carrier patients with estrogen receptor-negative breast cancer, with a haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 82 publications
0
3
0
4
Order By: Relevance
“…(2018) publicaron un estudio que incluyó 338 mujeres con CM y VP en BRCA1/2 cuya edad de diagnóstico fue de 35 y 37 años respectivamente (6) ; similar observación informan Muraren y col (2020) (22) . Por otra parte, otros autores, estudiaron mujeres con CM y CO con VP en BRCA1/2 y no observaron diferencias en la edad de diagnóstico entre los grupos de estudio (7,9,23) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(2018) publicaron un estudio que incluyó 338 mujeres con CM y VP en BRCA1/2 cuya edad de diagnóstico fue de 35 y 37 años respectivamente (6) ; similar observación informan Muraren y col (2020) (22) . Por otra parte, otros autores, estudiaron mujeres con CM y CO con VP en BRCA1/2 y no observaron diferencias en la edad de diagnóstico entre los grupos de estudio (7,9,23) .…”
Section: Discussionunclassified
“…Diferentes autores (8,23,24) mencionan en artículos de los últimos años, resultados similares en donde se destaca la presencia de tumores TN entre los casos con VP en BRCA1 en el 30-35%, y en BRCA2 en el 20%; observando que nuestro trabajo es concordante con la mayor frecuencia de CM triple negativo entre los casos con VP en BRCA1/2. Respecto a las VP halladas en la muestra, observamos que corresponden al 25% y el porcentaje de variantes noveles fue del 10,0%; estos resultados son consistentes con lo publicado por otros autores (16)(17)(22)(23)(24)26) . De las variantes nóveles, tres fueron en BRCA1 y sólo una fue en BRCA2.…”
Section: Discussionunclassified
“…Then, RNA is isolated for reverse transcription, and the chimeric transcripts generated from both wild-type and mutant constructs are compared by PCR and sequencing to determine splicing changes. Several studies have shown that the impacts of variants on splicing patterns and protein functions are not always equivalent; they can vary depending on the proportions of truncated and functional isoforms (37)(38)(39)(40).…”
Section: Vus and Synonymous Variants Reported In Databasesmentioning
confidence: 99%
“…Systemic injustices, like disparities in healthcare access, explain a substantial proportion of breast cancer outcome disparities (14)(15)(16)(17). Recent studies additionally suggest that germline genetic variation is associated with breast cancer outcomes, and these associations vary across ancestry groups (18)(19)(20)(21). In The Cancer Genome Atlas (TCGA), BW had substantially higher polygenic risk scores for the more aggressive ER-negative subtype than WW, suggesting differential genetic contributions for susceptibility for breast cancer, especially ER-negative breast cancer (21).…”
Section: Introductionmentioning
confidence: 99%